T3 THYROTOXICOSIS IN A PATIENT WITH METASTATIC FOLLICULAR THYROID CARCINOMA - Ching, Ling Jing; Ho, Jin Hui; Tee, Hwee Ching (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Differentiated thyroid cancers are usually associated with normal thyroid function. Rarely, thyrotoxicosis can develop due to functioning metastatic thyroid carcinoma. We present a case of a male with metastatic follicular thyroid cancer associated with T3 thyrotoxicosis. CASE A 57-year-old male with underlying multinodular goitre presented with rapidly enlarging neck swelling, heat intolerance, loose stools, weight loss, and left shoulder pain over three months’ duration. He exhibited a huge left goitre with right tracheal deviation. Laboratory tests revealed normal FT4, elevated FT3, and suppressed TSH. Thyroid ultrasound and contrast computed tomography (CT) scan unveiled a large left hemithyroid mass with retrosternal extension and contralateral tracheal displacement. Metastatic lesions were observed in the lungs, pleura, left scapula, cervical, and mediastinal lymph nodes. Needle aspiration of the thyroid mass showed a follicular nodule, while biopsy of the left scapula confirmed metastatic follicular thyroid carcinoma. The patient underwent total thyroidectomy with left modified radical neck dissection. Histopathologic examination revealed widely invasive follicular thyroid carcinoma, with areas of transformation to anaplastic thyroid carcinoma. CONCLUSION The coexistence of T3 thyrotoxicosis and thyroid cancer, particularly the follicular subtype, is uncommon and warrants careful consideration in clinical practice.